The Effect of Service Quality and Price Perception on Customer Loyalty Mediated by Customer Satisfaction at Bengkel Sukses Jaya - Valencia Livia; Hendratmoko Hendratmoko (Jurnal Indonesia Sosial Sains, 2024)
This research investigates the impact of service quality and price perception on customer loyalty, with customer satisfaction acting as a mediating variable at Bengkel Sukses Jaya. Utilizing a quantitative research approach, data were gathered from 106 respondents who have used or are currently using the motorcycle maintenance services at the workshop. The analysis was conducted using the PLS-SEM method through SmartPLS 4.1.0.3 software. Results reveal that both service quality and price perception significantly enhance customer satisfaction. Moreover, service quality directly fosters customer loyalty, while price perception shows no direct effect on loyalty. However, customer satisfaction emerges as a significant driver of customer loyalty. Notably, the study confirms that service quality and price perception indirectly influence customer loyalty through the mediating role of customer satisfaction.